2020
DOI: 10.24953/turkjped.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Assesment of colistin related side effects in premature neonates

Abstract: Background. Colistin is an antibiotic in the polymyxin group and is especially important in the elimination of multi-drug resistant gram negative bacteria. To date, there are many studies investigating colistin related side effects, especially nephrotoxicity. However, there are few studies involving premature neonates, and this study aimed to investigate the side effects of colistin in this particular patient group. Methods. Between January 2016 and May 2019, the medical records of premature neonates treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…2 Similar to the results of Kaya Aksoy G and colleagues as well as Alan S and colleagues magnesium levels of the cases in our study decreased significantly after the use of colistin. 1,3 Prolonged intolerance of the gastrointestinal system was a side effect unprecedented in other studies but was observed in 9.1% of cases in our study, which diminished alongside the discontinuation of colistin. 10 patients developed cholestasis, and although the clinical signs and symptoms subsided, total resolve occurred only after discontinuation.…”
Section: Dear Editorsupporting
confidence: 44%
See 1 more Smart Citation
“…2 Similar to the results of Kaya Aksoy G and colleagues as well as Alan S and colleagues magnesium levels of the cases in our study decreased significantly after the use of colistin. 1,3 Prolonged intolerance of the gastrointestinal system was a side effect unprecedented in other studies but was observed in 9.1% of cases in our study, which diminished alongside the discontinuation of colistin. 10 patients developed cholestasis, and although the clinical signs and symptoms subsided, total resolve occurred only after discontinuation.…”
Section: Dear Editorsupporting
confidence: 44%
“…We read with interest the recently published article by Kaya Aksoy G et al 1 in which the side effects associated with colistin use in premature infants were evaluated.…”
Section: Dear Editormentioning
confidence: 99%
“…Recent studies have reported an association between colistin-related nephrotoxicity and concurrent aminoglycoside use. 24,25 Aminoglycosides are among the most frequently used antibiotics in the NICU. While concurrent aminoglycosides were identified as an independent predictor of colistin-associated AKI, in some cases, the combination therapy of aminoglycosides and colistin is unavoidable.…”
Section: Discussionmentioning
confidence: 99%
“…Colistin seems to be a poor choice for patients due to severe side effects including nephrotoxicity, neurotoxicity (paresthesia, partial deafness, confusion, hallucinations, seizures, ataxia), and electrolyte imbalance. Significant side effects associated with colistin force physicians to treat infection caused by MDR pathogens using tigecycline ( Ordooei Javan et al., 2015 ; Aksoy et al., 2020 ). Adverse drug reactions of tigecycline are mild, including gastrointestinal problems (diarrhoea, nausea, vomiting), pancreatitis, fever, accompanied coinfections, thrombocytopenia, local reaction, and changes in hepatic functions (increased concentration of alanine transaminase and aspartate transaminase) ( Greer, 2006 ; Tasina et al., 2011 ).…”
Section: Development Of Mdr/xdr Strainsmentioning
confidence: 99%